Implementasi Simple Network Management Protocol (SNMP) pada Bot Monitoring Telegram - Muhammad Taruna Praja Utama; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
One useful network management function to determine whether the network is still practical, viable, or needs more capacity is network monitoring. If an administrator is looking to redesign an existing network, monitoring the results may also be helpful. Monitoring device status, such as CPU percentage, RAM, and traffic using SNMP, is one of many network monitoring techniques. To facilitate this monitoring process, it can be done remotely with a program that provides alert messages to the user. One of the communication media is using the Telegram application, Telegram also has bot facilities that can be programmed to run continuously without stopping. The purpose of the research is to find out how to design a monitoring bot program using SNMP that sends notification messages to Telegram and to find out how to test the Telegram monitoring bot program using SNMP.